Monitoring Sistem Kontrol Mesin Drying Kopi Secara Real Time Berbasis IoT - Kusmiyati, Kusmiyati; Pambudi, Arga Dwi; Arifin, Zaenal; Wulandari, Sari Ayu; Purnomo, Muhammad Agus; Setiadi, Kristoforus Ardian; Listianingrum, Nia Yunita (Elektrika, 2023)
The process of drying coffee beans often done by manually using sunlight which has its drawbacks, where coffee farmers cannot predict the weather which may rain at any time. If exposed to rain water, coffee beans that are slightly dry will become wet and moist again, which will affect the quality of the coffee beans. Therefore, in this research a literature study will be carried out, followed by the construction of an IoT-based coffee drying machine so that its condition can be monitored at any time. In the drying process, a PTC fan and heater will be used to regulate the temperature and humidity in the coffee drying machine to get better results in drying coffee. This research will also test how much temperature and humidity are optimal in the coffee drying machine, because it will also affect the drying time and the quality of the coffee produced. To determine the quality of the coffee beans and develop a coffee drying machine, researchers will collaborate with UKM Boyolali which has experience in drying coffee beans. IoT-based dying coffee machine has been made, with dimensions (80 x 47 x 115) cm, drying capacity of 30 grams, using electric fuel which is integrated with temperature and humidity sensors which function as drying temperature controllers, with measurement error calibration results of 1.2 and organoleptic tests show that the quality of the coffee produced by the tool/machine is better than the coffee produced by manual heating, where the coffee beans heated by the machine have a strong coffee aroma but do not smell burnt, the color is even, light brown in color and has a bitter taste and when crushed and dissolved there is no precipitate on the surface. The optimum temperature for the IoT-based dying coffee machine is 80ºC in 883 seconds or the equivalent of 15 minutes, which is equivalent to traditional drying by relying on sunlight for 10 days, while the optimal humidity for the IoT-based dying coffee machine is 15 %, this is in accordance with the quality standards of coffee as a result of heating.          Keywords: Coffee beans, Drying coffee machine, IoT ABSTRAK  Pada proses pengeringan biji kopi saat ini masih sering dilakukan secara manual menggunakan sinar matahari yang memiliki kekurangan, dimana petani kopi tidak bisa memprediksi cuaca yang kemungkinan bisa terjadi hujan setiap saat. Jika terkena air hujan biji kopi yang agak kering akan menjadi basah dan lembab kembali, dimana akan jadi berpengaruh pada kualitas dari biji kopi tersebut. Oleh karena itu pada penelitian ini akan dilakukan study literature, yang dilanjutkan dengan pembuatan mesin drying kopi berbasis IoT sehingga bisa dipantau kondisinya setiap saat. Pada proses pengeringan akan digunakan fan dan heater PTC untuk mengatur suhu dan kelembapan di dalam mesin drying kopi untuk mendapatkan hasil yang lebih bagus dalam pengeringan kopi. Pada penelitian ini juga akan diujikan seberapa besar suhu dan kelembapan yang optimal di dalam mesin drying kopi, karena akan berpengaruh juga pada waktu pengeringan dan kualitas kopi yang dihasilkan. Untuk menentukan kualitas dari biji kopi dan mengembangkan mesin drying kopi peneliti akan bekerjasama dengan UKM Boyolali yang sudah berpengalaman dibidang pengeringan biji kopi. Telah dibuat mesin dying kopi yang berbasis IoT, dengan dengan dimensi (80 x 47 x 115) cm, kapasitas pengeringan 30 gram, menggunakan bahan bakar listrik yang terintegrasi dengan sénsor suhu dan kelembaban yang berfungsi sebagai pengontrol suhu pengeringan, dengan hasil kalibrasi error pengukuran sebesar 1,2 dan uji organoleptic menunjukan bahwa kualitas kopi hasil alat/ mesin lebih bagus dibandingkan dengan kopi hasil pemanasan manual, dimana biji kopi hasil pemanasan dengan mesin mempunyai aroma kopi kuat namun tidak beraroma gosong, warna merata, berwarna coklat muda dan mempunyai rasa pahit dan ketika ditumbuk dan dilarutkan tidak ada endapan dipermukaan. Suhu optimal pada mesin dying kopi yang berbasis IoT adalah 80ºC dalam kurun waktu 883 detik atau setara dengan 15 menit yang mana hasil tersebut setara dengan pengeringan secara tradisional dengan mengandalkan sinar matahari selama 10 hari, sedangkan kelembapan optimal pada mesin dying kopi yang berbasis IoT adalah 15%, hal ini sesuai dengan baku mutu kopi hasil pemanasan.